KHILAFATISM IN ISLAM: THE CONCEPT OF THE KHILAFAH IN THE VIEW OF HIZBU TAHRIR AND AHMADIYAH - Muhammad Syaoki (UIN Mataram, 2021)
After the collapse of the Ottoman dynasty in Turkey, khilafatism became a prolongedpolemic in the Islamic world. This polemic gave rise to various movements includingHizb ut-Tahrir which emerged in Palestine and the Ahmadiyya which emerged in India.This research is a type of literature study using qualitative methods. The results of thisstudy indicate that although these two movements have completely different theologicalviews, they both carry the idea of a caliphate even though in practice these twomovements have different fighting directions. Khilafatism in Ahmadiyah has beenrunning for a long time and survived, while khilafatism in HT is still a kind of utopiabecause until now there has not been a single region that has implemented a caliphatesystem, especially in Indonesia after the establishment of HTI as a banned massorganization.